Contact resistivities of antimony-doped n-type Ge1−xSnx. (23rd June 2016) - Srinivasan, V S Senthil; Fischer, Inga A; Augel, Lion; Hornung, Anja; Koerner, Roman; Kostecki, Konrad; Oehme, Michael; Rolseth, Erlend; Schulze, Joerg
Abstract: As Ge1− x Sn x is being investigated for CMOS applications, obtaining contacts to n-type Ge1− x Sn x with low specific contact resistivity ( ρ c ) is a major concern. Here, we present results on specific contact resistivities of Sb doped n-type Ge1− x Sn x with 0 ≤ x ≤ 0.08 also with varying doping concentrations using Ni, Ag and Mn as contact metals. Our results show that Ni offers the lowest ρ c for all x values of Ge1− x Sn x . The lowest ρ c measured for Ni contacts on highly n-doped Ge0.92 Sn0.08 is 2.29 × 10 −6 Ω cm 2 . We find a strong dependence of the specific contact resistivity on doping, which we attribute to the fact that strong Fermi level pinning is present in metal/n-Ge1− x Sn x contacts.